Asymmetrical Cerebral Lateral Ventricles in Mild Cognitive Impairment and Alzheimer Disease - Khan, Amanda Farah; Bartha, Robert; Annweiler, Cedric (Archives of Clinical and Biomedical Research, 2024)
Background: Growing evidence suggests a right-less-than-left asymmetry in pathological process during the course of Alzheimer disease (AD) between brain hemispheres. The purpose of this study was to investigate the left versus right volumes of the lateral ventricles, an aggregate measure of brain matter loss, in older adults with normal cognition, mild cognitive impairment (MCI; i.e., prodromal AD) and AD. Methods: We studied 96 community-dwelling older participants (mean, 72.3±6.2years; 55.2% women) followed in the Memory Clinic of Angers University Hospital, France, as part of the GAIT study. Patients had their lateral ventricles volume quantified using semi-automated software from three-dimensional T1-weighted MRI. Results: We found a left-right asymmetric enlargement of the lateral ventricles in participants with MCI and AD, but not in cognitively healthy individuals. This asymmetry involved the main body volumes, but not the temporal horns. Conclusions: Our results add support to the assumption of an asymmetry of pathology in AD. Asymmetrical atrophy may serve as a potential biomarker of AD useful to discriminate between cognitively healthy individuals and those with AD.